B-mode ultrasonography and ecobiometric parameters for assessment of embryonic and fetal development in sheep - Correia Santos, Victor José [UNESP]; Garcia Kako Rodriguez, Mariana [UNESP]; del Aguila da Silva, Priscila [UNESP]; Sitta Gomes Mariano, Renata [UNESP]; Taira, Augusto Ryonosuke [UNESP]; de Almeida, Vivian Tavares [UNESP]; Ramirez Uscategui, Ricardo Andrés [UNESP]; Nociti, Ricardo Perecin [UNESP]; Maia Teixeira, Pedro Paulo; Rossi Feliciano, Marcus Antonio [UNESP]; Russiano Vicente, Wilter Ricardo [UNESP] (Elsevier, 2018)
The aim in this study was to evaluate the maternal-fetal development during physiological gestation in sheep by means of ultrasonography and to predict the gestational age by mathematical formulae. Thirty Santa Inês sheep were included. Evaluations were performed weekly from the 3rd to 21st gestational week. The Shapiro test was used to determine normality of the data, and Spearman test was used for determining correlations of real or transformed measurements as gestation advanced. If there was a significant difference detected, variable adjustments and gestational weeks were tested using regression models. Significance level was set at 5% and the results presented as mean ± SD. Principal components analysis (PCA) was used for data clustering and graphic analysis. The gestational vesicle, abdominal, thoracic, biparietal, ocular orbit, and placentome diameters; and the lengths of crown-to-rump, nuchal to snout, scapula, humerus, radius, metacarpus, femur, tibia, metatarsal, heart length, heart width and kidneys were measured. Using pulsed Doppler ultrasonography, heart rate (HR) was obtained. The greatest coefficients of determination (r²) were obtained for the biparietal diameter (BPD; 96.5%) and metacarpus length (MCAR; 93%), followed by the abdominal diameter (AD; 91.7%) and heart width (HTW; 90.2%). The PCA analysis indicated graphically that at week 8 to 9, there was no significant change related to technique, whereas, at weeks 19, 20, and 21 a decrease in growth was observed, with the greatest data variability at week 19. Ultrasonographic assessments indicated there were significant correlations between developmental stages of all maternal-fetal structures and the gestational age, which can be used as reference values for gestational age assessments and detection of development abnormalities.
Keywords: Development; Ewes; Gestation; Ultrasonography